2004
DOI: 10.1002/hep.20492
|View full text |Cite
|
Sign up to set email alerts
|

Role of hepatic fibrin in idiosyncrasy-like liver injury from lipopolysaccharide-ranitidine coexposure in rats

Abstract: Coadministration of nonhepatotoxic doses of the histamine 2-receptor antagonist ranitidine (RAN) and bacterial lipopolysaccharide (LPS) results in hepatocellular injury in rats, the onset of which occurs in 3 to 6 hours. This reaction resembles RAN idiosyncratic hepatotoxicity in humans. Early fibrin deposition occurs in livers of rats cotreated with LPS/RAN. Accordingly, we tested the hypothesis that the hemostatic system contributes to liver injury in LPS/RAN-treated rats. Rats were given either LPS (44.4 ؋ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
41
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 34 publications
7
41
0
Order By: Relevance
“…Lesions in livers of LPS/RAN-treated rats have been described previously (Luyendyk et al, 2003b) and were characterized by midzonal and subserosal hepatocellular oncotic necrosis and neutrophilic infiltrate (data not shown). Previous studies showed that the coagulation system is a critical mediator of LPS/RAN-induced liver injury (Luyendyk et al, 2004a). Confirming these results, serum ALT activity was significantly attenuated by heparin at 6 h (Fig.…”
Section: Resultssupporting
confidence: 83%
See 3 more Smart Citations
“…Lesions in livers of LPS/RAN-treated rats have been described previously (Luyendyk et al, 2003b) and were characterized by midzonal and subserosal hepatocellular oncotic necrosis and neutrophilic infiltrate (data not shown). Previous studies showed that the coagulation system is a critical mediator of LPS/RAN-induced liver injury (Luyendyk et al, 2004a). Confirming these results, serum ALT activity was significantly attenuated by heparin at 6 h (Fig.…”
Section: Resultssupporting
confidence: 83%
“…Indeed, liver hypoxia is observed at a time near the onset of hepatotoxicity in this model (Luyendyk et al, 2004a). Although these results are consistent with liver hypoxia as an important downstream deleterious consequence of hemostasis in LPS/RANtreated rats, a direct link between coagulation system activation and hypoxia has not yet been established in this model.…”
mentioning
confidence: 46%
See 2 more Smart Citations
“…Bacterial LPS (100 µg/kg, i.p), 28,29 was administered 2 hours before antimalarial drugs. Methyl palmitate (2 g/kg, i.v) was applied as an effective kupffer cells inhibitor and administered 44 hours before LPS.…”
Section: Methodsmentioning
confidence: 99%